2014
DOI: 10.1136/jmedgenet-2014-102405
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing of familial hypercholesterolaemia patients negative forLDLR/APOB/PCSK9mutations

Abstract: BackgroundFamilial hypercholesterolaemia (FH) is an autosomal dominant disease of lipid metabolism, which leads to early coronary heart disease. Mutations in LDLR, APOB and PCSK9 can be detected in 80% of definite FH (DFH) patients. This study aimed to identify novel FH-causing genetic variants in patients with no detectable mutation.Methods and resultsExomes of 125 unrelated DFH patients were sequenced, as part of the UK10K project. First, analysis of known FH genes identified 23 LDLR and two APOB mutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 36 publications
1
75
0
10
Order By: Relevance
“…PCSK9 mutations therefore occur in about 1% of this population. In a Dutch population [29] reported gene frequencies were LDLR, 95% and APOB, 5% with no gain of function PCSK9 discovered and in the UK LDL-R, 93%, APOB about 5% and gain of function PCSK9 1.7% [30]. Although the presence of a gain of function PCSK9 allele, which increases PCSK9 levels, in HoFH predicts a good response to PCSK9 inhibitors, response in the HoFH population is mainly determined by residual receptor activity [31].…”
Section: Diagnosis Of Hofhmentioning
confidence: 98%
“…PCSK9 mutations therefore occur in about 1% of this population. In a Dutch population [29] reported gene frequencies were LDLR, 95% and APOB, 5% with no gain of function PCSK9 discovered and in the UK LDL-R, 93%, APOB about 5% and gain of function PCSK9 1.7% [30]. Although the presence of a gain of function PCSK9 allele, which increases PCSK9 levels, in HoFH predicts a good response to PCSK9 inhibitors, response in the HoFH population is mainly determined by residual receptor activity [31].…”
Section: Diagnosis Of Hofhmentioning
confidence: 98%
“…21 The causes of the remaining cases of clinical FH remain obscure though some seem to be caused by mutations in apoB outside exon 26 or in other genes. 22 However studies of FH in children suggest that 95% of FH is potentially identifiable with the remainder of cases being caused by phenocopies of FH such as familial combined hyperlipidemia which share many clinical features with FH. 23 Analyses of the health economics of FH show that cascade screening is the optimal strategy to find cases of FH 24 and that comprehensive genetic typing allied with cascade family screening by genetic techniques is best 25 but value is also gained from lipid-related screening in those where mutations are not identified.…”
Section: Diagnosis Of Familial Hypercholesterolemiamentioning
confidence: 99%
“…Researchers have been actively searching for a mutation in an additional gene that could explain the genetic cause of mutationnegative FH cases [4e8]. Nevertheless, novel FH-causing genes still account for only fractional portions of genetically undefined FH patients, possibly due to allelic rarity or heterogeneity [4,9]. Recently, studies of European patients demonstrated that a subset of mutation-negative FH patients may have a polygenic cause [10,11].…”
Section: Introductionmentioning
confidence: 99%